Investigating Visfatin gene Polymorphism rs4730153 with Insulin Resistance and Non-Alcoholic Fatty Liver Diseases in Iranian Population - Somayeh Marjani; Masoumeh Nezhadali; Azadeh Hekmat; Marjan Zarif Yeganeh (Tehran University of Medical Sciences, 2022)
Background: Visfatin is known as one of the adipokines associated with the development of inflammation, but its role in the pathogenesis of nonalcoholic fatty liver is less known so far. We aimed to investigate the association between visfatin gene polymorphism rs4730153 and insulin resistance and non-alcoholic fatty liver disease (NAFLD). Methods: This case-control study was performed on 80 patients with NAFLD as well as 80 healthy participants as controls referred to Amir Al-Momenin and Bouali hospitals in Tehran. Genotyping was performed using PCR-RFLP method. Plasma concentrations of visfatin and insulin were measured using ELISA kit. The fasting blood glucose, TC, TG, LDL-C, HDL-C, ALT, AST, SBP, DBP, and BMI levels were measured using the standard methods. Statistical analysis was also performed using SPSS software. Results: A significant difference was found in Visfatin level in the patients with NAFLD compared to this level in healthy individuals. The levels of HDL-C and LDL-C in healthy individuals and triglyceride in patients for GG, AG, and AA genotypes carriers also were significantly different. There was a significant relationship between rs4730153 polymorphism and insulin resistance; however, no association was found between this polymorphism and NAFLD. Notably, Visfatin showed a significant association with age (all individuals), body mass index (healthy individuals), insulin, and HOMA (in patients). Conclusion: Visfatin levels reduced in patients with NAFLD. Moreover, rs4730153 polymorphism was indicated to be associated with both lipid metabolism and insulin resistance, but no association was found between this polymorphism and nonalcoholic fatty liver disease.